IgA nephropathy enigma - Mestecky, Jiri; Novak, Jan; Moldoveanu, Zina; Raska, Milan (Clinical immunology (Orlando, Fla.), 2016)
IgA nephropathy (IgAN) is the leading cause of primary glomerulonephritis in the world. The disease is characterized by the presence of IgA-containing immune complexes in the circulation and in mesangial deposits with ensuing glomerular injury. Although in humans there are two IgA subclasses, only IgA1 molecules are involved. The exclusivity of participation of IgA1 in IgAN prompted extensive structural and immunological studies of the unique hinge region (HR) of IgA1, which is absent in otherwise highly homologous IgA2. HR of IgA1 with altered O-glycans serves as an antigen recognized by autoantibodies specific for aberrant HR glycans leading to the generation of nephritogenic immune complexes. However, there are several unresolved questions concerning the phylogenetic origin of human IgA1 HR, the structural basis of its antigenicity, the origin of antibodies specific for HR with altered glycan moieties, the regulatory defects in IgA1 glycosylation pathways, and the potential approaches applicable to the disease-specific interventions in the formation of nephritogenic immune complexes. This review focuses on the gaps in our knowledge of molecular and cellular events that are involved in the immunopathogenesis of IgAN.
Keywords: Immunoglobulin A; modely nemocí na zvířatech; Glomerulonephritis, IGA; Humans; Autoimmunity; IgA glycans; IgA glycosylation; IgA subclasses; IgA hinge region; imunoglobulin A; IgA nefropatie; lidé; IgA nephropathy; Animals; Disease Models, Animal; zvířata; Animal models of IgA nephropathy